WEB-BASED TED-ED: BLENDED LEARNING IN TEACHING SPEAKING - Elisabeth Filadelfia, - (2021)
Web-Based TED-Ed is a learning platform that is created by a non-profit organization with 'ideas worth spreading' as a motto. This learning platform is considered helpful for teachers and students in both face-to-face and online learning, specifically in this recent pandemic situation. Furthermore, this study was analyzed qualitatively. In general, the results of this study show that blended learning and TED-Ed complete each other in improving student speaking skills. Changes appear in aspects of comprehension, pronunciation, vocabulary, and grammar. Meanwhile, the integration of TED-Ed and Blended Learning was challenging since it required creativity to integrate all activities, materials and time efficiency in virtual meeting. However, blended learning and TED-Ed require face to face non virtual to support improving aspects of fluency. But, for other speaking skills have positive changing after supported by Web-Based TED-Ed in learning for English subject of Industrial engineering major in one of the universities in Bandung with zoom application assistance. This collaborative action research was conducted in three cycles. In order to measure students' speaking development, the pre-test and post test were collected. Accordingly, this study found out that students speaking skills' scores changed into better scores after learning by using Web Based TED-Ed. Moreover, based on the interview, students dominantly admit that this learning tool helped them study at home as all features of TED-Ed guide them to have deep learning since TED-Ed is easy, simple, and fit for students' needs. In short, TED-Ed is recommended as a teaching medium in this online learning situation to support the needs of 21st-century students. Keywords: Blended-learning, speaking skills, Web-based TED-Ed.